1997
DOI: 10.1007/s001250050756
|View full text |Cite
|
Sign up to set email alerts
|

Total immunoreactive proinsulin, immunoreactive insulin and specific insulin in relation to conversion to NIDDM: the Mexico City Diabetes Study

Abstract: Non-insulin-dependent diabetes mellitus (NIDDM) is characterized by peripheral insulin resistance, beta-cell failure, and increased hepatic glucose production [1]. In diabetic subjects, these metabolic abnormalities interact in a complex fashion to cause and sustain hyperglycaemia. However, there continues to be controversy about which of these abnormalities is primary. Both insulin resistance [2] and deficient insulin secretion [3] have been postulated as antecedents of NIDDM. Prospective studies are useful i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
57
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 48 publications
4
57
0
Order By: Relevance
“…A similar phenomenon was reported by Lillioja et al (7) in a prospective study of Pima Indians. Our observation that elevated baseline PI concentration, a measure of ␤-cell dysfunction, was a significant independent predictor of diabetes is consistent with previous studies that were conducted in populations of European white (18,19,23), Asian (17,22), Asian-American (20), and Mexican origin (21). The present results contribute to this body of literature in a number of ways.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A similar phenomenon was reported by Lillioja et al (7) in a prospective study of Pima Indians. Our observation that elevated baseline PI concentration, a measure of ␤-cell dysfunction, was a significant independent predictor of diabetes is consistent with previous studies that were conducted in populations of European white (18,19,23), Asian (17,22), Asian-American (20), and Mexican origin (21). The present results contribute to this body of literature in a number of ways.…”
Section: Discussionsupporting
confidence: 93%
“…PI and its split products circulate in high concentrations in subjects with diabetes and gestational diabetes (12)(13)(14), as well as (in some studies) among individuals with IGT or a diabetic first-degree relative (12,15,16). In addition, a limited number of investigations have reported that elevated absolute and relative concentrations of PI and its split products are prospectively associated with risk of diabetes (17)(18)(19)(20)(21)(22)(23). Finally, recent studies have shown that PI and the PI-to-insulin ratio correlate significantly with AIR (24,25).…”
Section: -1270 2002mentioning
confidence: 99%
“…This measurement is commonly regarded as a marker of inappropriate intracellular processing of pro-hormone to insulin and, by extension, as a generic index of beta cell dysfunction. Interestingly, fasting proinsulin is already markedly elevated in subjects with normal glucose tolerance who develop diabetes at follow-up [23].…”
Section: Fasting Plasma Insulinmentioning
confidence: 99%
“…Although the cause of disproportional hyperproinsulinaemia in diabetes is unknown, it may arise from inefficient proinsulin processing within the beta cell secretory granule or the premature release of proinsulin as a result of increased demand for insulin in insulin-resistant states [4]. Elevations in the ratio of proinsulin to insulin as well as absolute proinsulin concentrations adjusted for fasting insulin have been proposed as early markers of beta cell dysfunction [5].…”
Section: Introductionmentioning
confidence: 99%